First, we will expand the terms in parenthesis:

#m + color(red)(4)(2m - 3) = -3#

#m + (color(red)(4) xx 2m) - (color(red)(4) xx 3) = -3#

#m + 8m - 12 = -3#

We can now combine like terms:

#1m + 8m - 12 = -3#

#(1 + 8)m - 12 = -3#

#9m - 12 = -3#

Next we can isolate the #m# term and keep the equation balanced by adding #color(red)(12)# to each side of the equation:

#9m - 12 + color(red)(12) = -3 + color(red)(12)#

#9m - 0 = 9#

#9m = 9#

Now we can solve for #m# while keeping the equation balanced by dividing each side of the equation by #color(red)(9)#:

#(9m)/color(red)(9) = 9/color(red)(9)#

#(color(red)(cancel(color(black)(9)))m)/cancel(color(red)(9)) = 1#

#m = 1#